Administration of heat killed Fructobacillus fructosus OS-1010 attenuates metabolic disease induced by high fat diet in mice - Yoshiyuki Nakano; Ryosuke Nakamura; Hina Tanaka; Yuji Tokimoto; Yuna Masuda; Noriaki Emoto; Kouji Nishikawa; Hideaki Idogaki (Scientific Reports)
Abstract Heat-killed Fructobacillus fructosus OS-1010 reportedly enhance the number and membrane potential of mitochondria in muscle cell C2C12 in vitro. However, there are no reports on the effects of this strain on mitochondria or the resulting effects on the body in animal models. In this study, we investigated the effects of heat-killed F. fructosus OS-1010 on obesity and other metabolic abnormalities and muscle weakness in mice with high-fat diet (HFD)-induced sarcopenic obesity. C57BL/6 mice were fed HFD supplemented with heat-killed F. fructosus OS-1010 for 13 weeks. The HFD-induced body weight gain was significantly reduced. Additionally, there was a significant decrease in alanine aminotransferase levels, improvement in serum lipid profiles, and a reduction in non-alcoholic fatty liver disease (NAFLD) progression. Skeletal muscle weakness was also mitigated, with changes in gene expression in the quadriceps indicating suppression of intramuscular fat accumulation, and enhancement of mitochondrial density. The findings of this study suggest that heat-killed F. fructosus OS-1010 functions as an anti-obesity postbiotic, potentially benefiting both NAFLD and muscle weakness associated with obesity.